Research Progress on the Evaluation of Tourism Climate Comfort and Its Application in China: A Bibliometrics-Based Review - Xin Huang; Yi Hui; Junkai Chen; Zhixuan Huang; Ximei Li; Xitian Yang (Atmosphere, 2025)
The evaluation of tourism climate comfort is a systematic assessment of the climate conditions of tourist destinations. It is of great significance for improving the tourism experience, promoting the sustainable development of the tourism industry, and protecting the natural environment. In this study, the CiteSpace software was used to conduct a bibliometrics analysis of the study on tourism climate comfort in China, and the conceptual framework of this study was established based on the bibliometrics results. In the conceptual framework, this study firstly summarized eight indicators widely used in the current evaluation of tourism climate comfort. Secondly, four key technical means in the evaluation process were summarized, including geographic information system, analytic hierarchy process, fuzzy comprehensive evaluation, and cluster analysis. And three calculation methods of tourism climate comfort period were summarized, namely number of days with comfortable climate, five-day moving average method, and probability of climate-suitable days. Subsequently, the main application areas of tourism climate comfort evaluation were introduced: (1) exploration of the relationship between climate comfort and tourism activities (i.e., heat/cold-escape tourism, ice-snow tourism, outdoor rafting, coastal tourism, and other types of tourism activities); (2) exploration of the relationship between climate comfort and tourist flow; (3) the response of climate comfort to climate change; and (4) tourism climate regionalization. Finally, the main problems of current research and future development directions were proposed.